2016
DOI: 10.1016/j.toxrep.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-endocrine effects of aqueous extract of Amaranthus viridis (Linn.) leaf in male Wistar rat model of cyclophosphamide-induced reproductive toxicity

Abstract: Cyclophosphamide (CP) is a widely used cytotoxic alkylating agent with antitumor and immunosuppressant properties that is associated with various forms of reproductive toxicity. The significance of natural antioxidants of plant origin should be explored, especially in a world with increasing incidence of patients in need of chemotherapy. The neuro-endocrine effects of aqueous extract of Amaranthus viridis (Linn.) leaf (AEAVL) in Wistar rats with CP-induced reproductive toxicity was determined. Forty rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…There is little understanding of the influence of alkylating agents on the pituitary. Some previous studies reported that cyclophosphamide induced oxidative stress in the brain of mice [22,23], and Ayoka et al reported that the parenchymal cells appeared scanty and hypertrophied in the pituitary of mice exposed to cyclophosphamide [24]. We deduced that the alteration of the histoarchitecture of the pituitary may lead to GHD.…”
Section: Discussionmentioning
confidence: 64%
“…There is little understanding of the influence of alkylating agents on the pituitary. Some previous studies reported that cyclophosphamide induced oxidative stress in the brain of mice [22,23], and Ayoka et al reported that the parenchymal cells appeared scanty and hypertrophied in the pituitary of mice exposed to cyclophosphamide [24]. We deduced that the alteration of the histoarchitecture of the pituitary may lead to GHD.…”
Section: Discussionmentioning
confidence: 64%
“…Reduced glutathione (GSH) is a non‐enzymatic antioxidant marker, while thiobarbituric acid reactive substance (TBARS) is an important index of lipid peroxidation . This study demonstrated that cimetidine administration caused deleterious disturbance of the antioxidant system.…”
Section: Discussionmentioning
confidence: 97%
“…This suggested that AECUL boosted sperm counts by providing protection against the effects of cimetidine. Sperm motility and viability are also important and integral parameters of many reproductive toxicity guidelines . These sperm characterization indices can be affected when a chemical agent penetrates the blood‐testis barrier to cause deleterious changes in the micro‐environment of the seminiferous tubules .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacological activities of the extract, as demonstrated by vasodilatory and antioxidant-boosting potentials were conferred by its important phytochemicals such as flavonoids, phenolics alkaloids and tannins (Table 3). According to literature, these phytochemicals are reputed to demonstrate antioxidant, anti-inflammatory and membrane-stabilizing properties both invivo and invitro [58][59][60].…”
Section: Discussionmentioning
confidence: 99%